Dynamics of the foreshock compressional boundary and its connection to foreshock cavities. Issue 2 (28th February 2013) - Omidi, N.; Sibeck, D.; Blanco‐Cano, X.; Rojas‐Castillo, D.; Turner, D.; Zhang, H.; Kajdič, P.
Abstract: [1] We use several global hybrid (kinetic ions, fluid electrons) simulation runs for steady and time‐varying interplanetary magnetic field (IMF) conditions to examine the dynamics of the foreshock compressional boundary (FCB) and its connection to foreshock cavities. The results demonstrate that for steady IMF conditions, the FCB forms and evolves over a long period of time due to the dynamics of the bow shock and ion foreshock. Formation of the FCB is tied to the generation and nonlinear evolution of ULF waves associated with large‐amplitude fluctuations in magnetic field and density within the foreshock. As a result, even during steady IMF conditions, the transitions in the magnetic field strength and direction across an FCB evolve. Although the FCB itself is associated with increases in the magnetic field strength and density, these quantities are reduced on the turbulent side of the FCB as compared to the pristine solar wind. Hybrid simulations with time‐varying IMF have been performed to examine the relationship between the FCB and foreshock cavities generated under two possible scenarios. In the first scenario, a bundle of field lines connects to an otherwise quasi‐perpendicular bow shock and results in the formation of a finite‐sized foreshock region that travels with this bundle of field lines as it connects to different parts of the bow shock surface. Two FCBs bound the traveling foreshock region. In the second scenario, solar wind discontinuities cause the IMF cone angle (angle between the IMF and the solar wind flow direction) to vary and thereby modify the foreshock geometry and the position of the FCB. We demonstrate that structures similar to foreshock cavities bounded by FCBs form in both scenarios. We show that the two scenarios cannot be distinguished based on convecting or nonconvecting FCBs. We also demonstrate that depending on spacecraft location and the nature of the solar wind discontinuities, foreshock cavities may be bounded by an FCB on one side and a foreshock bubble on the other. Key Points: The foreshock compressional boundary is highly dynamic FCBs are associated with foreshock cavities under both generation mechanisms Foreshock cavities may have convective or non‐convective signatures